Comparative Efficacy and Safety of Two Different Formulations of Linear Hyaluronic Acid in Patients with Knee Osteoarthritis - Vincenzo Rania; Cristina Vocca; Gianmarco Marcianò; Maria Cristina Caroleo; Lucia Muraca; Emanuele Toraldo; Francesca Greco; Caterina Palleria; Gian Pietro Emerenziani; Luca Gallelli (Pharmaceuticals, 2025)
Introduction: Knee osteoarthritis (OA) is defined by articular cartilage loss, increased discomfort, and functional restrictions. Changes in lifestyle, painkillers, intra-articular injections, and, as a last resort, surgery are all part of clinical therapy. In this setting, intra-articular injections of hyaluronic acid (HA) represent a relevant and diffused therapeutic option. Materials and Methods: A prospective observational study was performed from October 2024 to May 2025 in 70 patients with knee OA. HA was administered in three intra-articular injections and was followed up at 3 and 6 months from the last injection. Knee Injury and Osteoarthritis Outcome Score (KOOS) was evaluated as primary outcome measure; Visual Analogue Scale (VAS), time up and go test, six-minute walking test, general health assessment with 36-Item Short Form Health Survey (SF-36), Zung’s Self-Rating Anxiety Scale (Zung SAS), and Zung’s Self-Rating Depression Scale (Zung SDS) as secondary outcome measures. Results: We observed a statistically significant improvement in clinical scores at 3 months in both HA formulations compared to the control group. No relevant side effects were described during the study. Conclusion: Hyalubrix 30 mg/2 mL and DIART 1.8%/2 mL are two safe and effective therapeutic options to manage knee OA, offering benefits in pain control, functionality and emotional wellness.